Palatovelars before syllabic resonants: another look - Kortlandt, Frederik (Baltistica, 2013)
We arrive at the following relative chronology: 1. Depalatalization before syllabic *r̥ (Proto-Indo-European), 2. Depalatalization before syllabic *l̥ (Balto-Slavic, Albanian, Armenian), 3a. Rise of an epenthetic vowel before syllabic nasals (Balto-Slavic, Armenian), 3b. Depalatalization before syllabic nasals (Albanian), 4. Rise of an epenthetic vowel before syllabic nasals (Albanian).